10. AUDIT CITRA PEMERINTAHAN PRESIDEN SUSILO BAMBANG YUDHOYONO DAN WAKIL PRESIDEN JUSUF KALLA - Pitakola, Dyah; Naryoso, Agus; Al Hayuantana, Bayu Vita (FORUM, 2007)
Politics, as communication, is a process, and just like communiaction it involves an inclusive conservation through the exchange of symbols, pictures, body languages, attitudes, manners, etc. Politics is not simply a form of communication, but more it is related to political experience that allow everybody to communicate with others. Political words creates image about object and the condition within conflict and social collaboration, therefore political conservation become a very important point in developing political image. Through the strong political image, politicians and government officers could reassure and motivate people to get involve in the activities and decison making process.